Navigating geopolitical realities: The EU's strategic positioning in the South Caucasus and Central Asia - Tengiz Pchaladze (European Centre for International Political Economy (ECIPE), 2025)
This policy brief examines the strategic importance of the South Caucasus and its pivotal role in the European Union's evolving engagement with Central Asia. The regional landscape, however, remains highly volatile. Russia's aggression in Ukraine has had direct and indirect repercussions for the South Caucasus. Against the backdrop of the war, Moscow continues its efforts to maintain the region within its sphere of influence - through military presence, disinformation, economic leverage, and political interference. Twenty percent of Georgia's territory remains illegally occupied by Russian forces, while the fragile post-conflict environment following the Second Karabakh War continues to shape relations between Armenia and Azerbaijan. While missions such as EUMM in Georgia and EUMA in Armenia reflect the EU's growing political engagement, they remain limited in scope and capacity, constraining the Union's ability to address the region's evolving risks (...)
Keywords: 330; EU-Außenpolitik; Kaukasus; Zentralasien